Improving the rectification of optical devices with laser pointers - Radonjić, Vojkan M.; Resimić, Branko V. (Vojnotehnički glasnik / Military Technical Courier, 2017)
This paper is based on the observations of prescribed actions during the maintenance of artillery weapons and immediately prior to the execution of combat firing. Adjusting the parallelism of the axes of the optical devices and the axis of the artillery barrel directly affects shooting accuracy.With a new method of parallel axes alignment, based on the use of laser pointers, the axis parallelism deviation is reduced to a minimum, which improves the precision of artillery firing. Reliable, easier and faster check of the axes parallelism is enabled as well as axes alignment with the artillery barrel axis.
Keywords: laser marker; optical axis; stripper